Flexible Lead-Free Ba0.5Sr0.5TiO3/0.4BiFeO3-0.6SrTiO3 Dielectric Film Capacitor with High Energy Storage Performance - Wenwen Wang (MDPI AG, 2021)
Ferroelectric thin film capacitors have triggered great interest in pulsed power systems because of their high-power density and ultrafast charge–discharge speed, but less attention has been paid to the realization of flexible capacitors for wearable electronics and power systems. In this work, a flexible Ba0.5Sr0.5TiO3/0.4BiFeO3-0.6SrTiO3 thin film capacitor is synthesized on mica substrate. It possesses an energy storage density of Wrec ~ 62 J cm−3, combined with an efficiency of η ~ 74% due to the moderate breakdown strength (3000 kV cm−1) and the strong relaxor behavior. The energy storage performances for the film capacitor are also very stable over a broad temperature range (−50–200 °C) and frequency range (500 Hz–20 kHz). Moreover, the Wrec and η are stabilized after 108 fatigue cycles. Additionally, the superior energy storage capability can be well maintained under a small bending radius (r = 2 mm), or after 104 mechanical bending cycles. These results reveal that the Ba0.5Sr0.5TiO3/0.4BiFeO3-0.6SrTiO3 film capacitors in this work have great potential for use in flexible microenergy storage systems.